2005
DOI: 10.1079/joh2005300
|View full text |Cite
|
Sign up to set email alerts
|

Clonorchiasis: an update

Abstract: Clonorchis sinensis, the Chinese or oriental liver fluke, is an important human parasite and is widely distributed in southern Korea, China (including Taiwan), Japan, northern Vietnam and the far eastern part of Russia. Clonorchiasis occurs in all parts of the world where there are Asian immigrants from endemic areas. The human and animal reservoir hosts (dogs, pigs, cats and rats) acquire the infection from the ingestion of raw fish containing infectious metacercariae. The first intermediate snail hosts are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
204
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(210 citation statements)
references
References 51 publications
4
204
1
1
Order By: Relevance
“…In China, clonorchiasis prevails mainly in Guangdong, Guangxi, and Heilongjiang provinces. The main reason for this is the consumption of raw fish and crustaceans (1)(2)(3)(4). In the province of Guangdong, epidemiological surveys were carried out in 62 of 95 counties from 1997 to 2003.…”
mentioning
confidence: 99%
“…In China, clonorchiasis prevails mainly in Guangdong, Guangxi, and Heilongjiang provinces. The main reason for this is the consumption of raw fish and crustaceans (1)(2)(3)(4). In the province of Guangdong, epidemiological surveys were carried out in 62 of 95 counties from 1997 to 2003.…”
mentioning
confidence: 99%
“…We conclude that these domestic animals, especially dogs and pigs, play a major role in the epidemiology of FZT in aquaculture. Although reports from other Southeast Asian countries have suggested that nonhuman reservoir hosts play only a minor role in the epidemiology of liver fl ukes, specifi c studies on the role of reservoir hosts, other than ours, have not been carried out (1,13,14). One limitation of our study is that the use of 2 different methods to obtain prevalence data from humans (5) and domestic animals may have introduced a bias when comparing the relative contributions of the eggs to the environment.…”
Section: Discussionmentioning
confidence: 92%
“…Biliary obstruction, intrahepatic stone formation, cholangitis, cholecystitis, cholelithiasis, biliary and liver abscesses, pancreatitis, and hepatitis are further severe symptoms. An increased risk of developing cholangiocarcinoma, a malignant tumor that arises from any portion of the bile ducts, is the most important clinical manifestation (58,85,91,92). C. sinensis has been classified by the International Agency for Research on Cancer (IARC) as a probable carcinogen (group 2A) (58).…”
Section: Clonorchis Sinensismentioning
confidence: 99%